Overuse injuries in children and adolescents - DiFiori, J. P. (The Physician and Sportsmedicine, 1999)
With the growth of youth sports programs, overuse injuries in young people have become common. Making the diagnosis can be challenging, but often the real hurdles are in identifying the causes of injury. Growth-related factors require special considerations in injury management. A directed history assessing these and other causative factors and a systematic exam help formulate a comprehensive rehabilitation program. Recommendations for a successful return to activity and prevention of reinjury include avoiding heavy training loads and early sport-specific training, taking adequate rest periods, and ensuring proper supervision.